Problems faced and coping strategies adopted by parents of the children with special needs in Pondicherry: A mixed method study - Boovaragasamy, Chithra; A.G, Keerthi; Boratne, Abhijit Vinodrao; Bahurupi, Yogesh Arvind; Seetharaman, N (Indian Journal of Community Health, 2019)
Background: The parents of a special child face different set of problems and needs to adopt different coping strategies that helps to eliminate, modify or manage a stressful event or crisis situation. Aims & Objectives: To determine the various problems faced and the coping strategies adopted by the parents of special children in Puducherry. Material & Methods: A cross-sectional study was conducted in the selected special schools of Puducherry during May 2017 to June 2017. Quantitative component included pre-tested semi structured and self-reported “F-COPES” (Family Crisis Oriented Personal Evaluation Scale) questionnaire after obtaining informed consent. Focus group discussions (qualitative data) were conducted among parents for more information on their problems and coping strategies adopted. Data was entered in EpiData 3.1 and analyzed using Epidata 2.2.2.182 software. Results: Among 187 participants, 70.6% were mothers. Majority of them reported problems like depression (69%) followed by economical issues (26.7%) and emotional disturbances (23.5%). The two most coping strategies used by the parents were having the strength within the family to solve problems (80.2%) and accepting that difficulties occur unexpectedly (78.6%). Conclusion: Depression was one of the major problems faced. Reframing and acquiring social support were the most commonly used coping strategies.